2018
DOI: 10.3168/jds.2018-14412
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: The effect of delayed colostrum feeding on plasma concentrations of glucagon-like peptide 1 and 2 in newborn calves

Abstract: Glucagon-like peptide (GLP)-1 is involved in glucose homeostasis via its role in stimulating insulin secretion, whereas GLP-2 increases mucosal growth of the small intestine. To our knowledge, the effect of delayed colostrum feeding on plasma GLP-1 and GLP-2 in neonatal calves has not been evaluated. To investigate the effect of delayed colostrum feeding on plasma concentrations of GLP-1 and GLP-2 in newborn calves, we randomly assigned 27 Holstein bull calves to 1 of 3 treatment groups: those fed colostrum wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…It was reported that circulating level of GLP‐2 was increased approximately 2 hr after nutrient ingestion as a result of nutrients arriving in the distal intestine (Connor, Evock‐Clover, Walker, Elsasser, & Kahl, ). In addition, our previous study reported that rise in plasma GLP‐2 concentration was observed within 6 hr after feeding in neonatal calves (Inabu et al, ). In the current study, all blood samples were collected 4 hr after MR feeding, and no treatment effect was observed for plasma GLP‐2 concentration after weaning period (at 63, 70, and 77 days after birth; data not shown), thus greater plasma GLP‐2 concentration for TB calves until weaning should be attributed to treatment effect.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…It was reported that circulating level of GLP‐2 was increased approximately 2 hr after nutrient ingestion as a result of nutrients arriving in the distal intestine (Connor, Evock‐Clover, Walker, Elsasser, & Kahl, ). In addition, our previous study reported that rise in plasma GLP‐2 concentration was observed within 6 hr after feeding in neonatal calves (Inabu et al, ). In the current study, all blood samples were collected 4 hr after MR feeding, and no treatment effect was observed for plasma GLP‐2 concentration after weaning period (at 63, 70, and 77 days after birth; data not shown), thus greater plasma GLP‐2 concentration for TB calves until weaning should be attributed to treatment effect.…”
Section: Resultsmentioning
confidence: 91%
“…A treatment effect was observed for plasma GLP‐2 concentration ( p = 0.02): mean plasma concentration of GLP‐2 among whole period was significantly higher for TB (0.60 ± 0.05 ng/ml) compared with CON (0.41 ± 0.05 ng/ml). In our previous studies, it was indicated that plasma GLP‐2 concentration was affected by feeding method of first colostrum (Inabu et al, , ). As described above, feeding method of colostrum feeding is similar among dairies and serum total protein concentration and albumin‐globulin ratio did not differ between treatment groups, thus, greater GLP‐2 concentration for TB from 7 days after birth may not be due to difference in feeding method of colostrum.…”
Section: Resultsmentioning
confidence: 98%
“…Hammon et al (2013) reported that ingested colostrum enhanced glucose uptake via the improved absorptive capacity of the GIT. In addition, it has been reported that colostrum intake increased plasma concentration of insulin, which is involved in glucose homeostasis (Hammon et al, 2000;Inabu et al, 2018). In the previous study, amount, timing, and frequency of colostrum intake affected insulin secretion in calves (Hadorn et al, 1997;Hammon and Blum, 1998).…”
Section: Introductionmentioning
confidence: 83%
“…Glucagon-like peptide-1 (GLP-1) is a gut-derived peptide secreted from intestinal L-cells in response to nutrient absorption from the intestine (Connor et al, 2015;Inabu et al, 2017Inabu et al, , 2018. Glucagon-like peptide-1 is involved in glucose homeostasis via the stimulation of insulin secretion in both nonruminants (O'Halloran et al, 1990;Holz et al, 1993) and ruminants (Faulkner, 1991;Edwards et al, 1997;Fukumori et al, 2012) as well as its own direct action without mediating insulin action (Luque et al, 2002;Acitores et al, 2005;Sancho et al, 2005Sancho et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to containing bioactive molecules, the consumption of colostrum also stimulates endogenous production of beneficial hormones that assist in the maturation of the GIT. For instance, Inabu et al (2018) demonstrated that plasma glucagon-like peptide-1 and -2 concentrations increase after colostrum feeding and that glucagon-like peptide-1 concentration was lower for calves not fed colostrum until 12 h of life compared with calves fed immediately after birth. As glucagon-like peptide-1 and -2 play a key role in glucose homeostasis (Fukumori et al, 2012) and stimulating gastrointestinal growth (Taylor-Edwards et al, 2011), respectively, it is clear that the feeding of colostrum has beneficial effects on gut development and furthers our understanding on the role of gut-derived peptides and their potential implications for the improvement of calf health and performance (Inabu et al, 2018).…”
Section: Colostrum Feedingmentioning
confidence: 99%